宣威地区所产烟煤燃烧产出可吸入细颗粒物与肺癌发病的关系研究 (Zhongguo Fei Ai Za Zhi, 2015)
BACKGROUND AND OBJECTIVE: The high incidence of lung cancer in Xuanwei, China, has become an important restricting factor for livelihood development, thus exerting local social and economic impacts. Coal is the main fuel of the local community and also the main source of indoor pollution. This study aims to explore the coal combustion inhalable fine particulate matter (PM2.5) and its component output differences in different areas of Xuanwei, Yunnan. Moreover, the aim of this study is to investigate the relationship between inhalation of fine particles and high incidence of local lung cancer. METHODS: For combustion test, coal mines designated as C1, K7 and M30 were collected from LaoLin Colliery of Laibing Town, Huchang Colliery of Baoshan Town, and Taiping Colliery of Wenxing Town in Xuanwei, respectively. PM2.5 of indoor air was weighed, analyzed for elemental composition, and morphologically compared. The pathological specimen of lung cancer patients in Xuanwei who underwent operation was observed through electron microscope. RESULTS: The PM2.5 concentrations in indoor air were (8.244 ±1.460) mg/m(3) (C1), (5.066±0.984) mg/m(3) (K7), and (5.071±1.460) mg/m(3) (M30). The differences among pairwise comparisons were statistically significant (P=0.029). The filter impurities of C1 coal seam primarily include Si-and O-enriched compounds. Moreover, three membranes that comprised other elements, including C, S, and Si, were observed. These membranes were evident from the aggregation of silica and a Ca-Al membrane. Compared with that of other coal seams, C1 coal generated a mass of impurities, in which several particles have irregular shape. We found nanoscale fine particles in some specimens of Xuanwei lung cancer patients. CONCLUSION: The produced combustion of C1 coal was different from that of K7 and M30 coal. PM2.5 composition may be associated with the high local incidence of lung cancer.